Perbaikan dan Perawatan Instalasi Penerangan serta Membuat Sistem Informasi Berbasis Text LED P10 Di Mts Nurul Falah Telok Pakedai Kabupaten Kubu Raya - Hasan Hasan; Wawan H; Satriyo Satriyo; M. Ilyas H.K. M. Ilyas H.K.; Rianda Rianda; Wendi Y. Wendi Y.; Irawan S. Irawan S.; Yohanes C. Yohanes C.; Teguh M. Teguh M.; Yusril E. Yusril E. (Politeknik Negeri Pontianak, 2026)
This community service activity aims to address vital infrastructure problems at MTS Nurul Falah, Telok Pakedai, Kubu Raya Regency, namely inadequate lighting installations and the lack of digital information media. The implementation team has successfully repaired points of damage in the school building so that the electrical installation network can operate normally and safely. In addition, the team has also successfully installed 2 units of new solar panel-based street lighting to illuminate the school yard. Meanwhile, the information system facilities with a 2x6 running text panel have been successfully created and operated for the purpose of school activity information, and a 1x6 running text panel has also been successfully created and operated for the mosque clock, which is installed inside the mosque. Overall, the PKM activities at Nurul Falah Mosque in Teluk Pakedai have been successfully carried out, has provided a comprehensive solution in improving the learning process at the madrasa. Thus, the PKM activities have created a safer and more informative environment, as well as enhanced the effectiveness of teaching and learning activities at the MTS.